Inverse optimal formation control of mobile agents with collision avoidance driven by Lévy processes. (September 2020) - Do, K.D.
Abstract: This paper formulates and solves a new problem of formation control for a group of second-order dynamic mobile agents with collision avoidance driven by Lévy processes with unknown characteristics. First, a new result on inverse optimal control design for nonlinear systems driven by Lévy processes without having to solve a Hamilton–Jacobi–Bellman equation or a Hamilton–Jaccobi–Isaacs equation is developed. Second, the newly developed result together with the Lyapunov direct and backstepping methods, and potential functions will be then used to solve the posed inverse optimal formation control problem for the mobile agents with limited sensing ranges.